Charisma Behind Bars: The Dynamics of “Jago Leadership” Among Inmates at Ambarawa Prison - Fathimah Nuur Ramadhanni; Kuncoro Bayu Prasetyo (Universitas Tribhuwana Tungga Dewi, 2026)
Within the social structure of correctional institutions, informal leadership is a dynamic that cannot be ignored, particularly with regard to figures often referred to as “jago” among inmates. This study aims to analyze the existence and characteristics of “jago” leadership at the Ambarawa Correctional Institution and to identify the factors that influence its emergence. The study employed a descriptive qualitative approach with informants selected through purposive sampling. Data were collected through in-depth interviews and observations of cell leaders, inmates, and the dynamics of social life at the Ambarawa Correctional Institution. Data validity was tested using triangulation. Data analysis was conducted through data reduction, thematic categorization, and interpretation based on the study’s focus. The results of the study reveal a discrepancy between the conditions openly described and the social reality within the prison. Inmates tend to deny the existence of “jago” figures, but observations indicate the presence of individuals who are more respected and wield social influence. The characteristics of these figures include communication skills, responsibility, experience, and the ability to maintain a conducive environment. Their emergence is influenced by social closeness, experience serving a sentence, and the trust of fellow inmates. Informal leadership coexists with formal rules without showing open conflict. These findings enrich the study of informal leadership by demonstrating that the legitimacy of “jago” figures is built through social trust, experience, and collective recognition, thereby supporting the creation of social order in the lives of inmates.Dalam struktur sosial lembaga pemasyarakatan, kepemimpinan informal menjadi dinamika yang tidak dapat diabaikan, khususnya terkait figur yang kerap diasosiasikan sebagai jago di kalangan narapidana. Penelitian ini bertujuan menganalisis keberadaan dan karakteristik kepemimpinan jago di Lembaga Pemasyarakatan Ambarawa serta mengidentifikasi faktor-faktor yang memengaruhi kemunculannya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pemilihan informan melalui purposive sampling. Data dikumpulkan melalui wawancara mendalam dan observasi terhadap kepala kamar, warga binaan pemasyarakatan, serta dinamika kehidupan sosial di Lapas Ambarawa. Keabsahan data diuji menggunakan triangulasi. Analisis data dilakukan melalui reduksi data, kategorisasi tematik, dan interpretasi berdasarkan fokus penelitian. Hasil penelitian menunjukkan adanya perbedaan antara kondisi yang disampaikan secara terbuka dengan realitas sosial di dalam lapas. Warga binaan cenderung menyangkal keberadaan figur jago, tetapi observasi menunjukkan adanya individu yang lebih disegani dan memiliki pengaruh sosial. Karakteristik figur tersebut meliputi kemampuan berkomunikasi, tanggung jawab, pengalaman, serta kemampuan menjaga situasi tetap kondusif. Kemunculannya dipengaruhi oleh kedekatan sosial, pengalaman menjalani pidana, dan kepercayaan sesama warga binaan. Kepemimpinan informal berjalan berdampingan dengan aturan formal tanpa menunjukkan pertentangan terbuka. Temuan ini memperkaya kajian kepemimpinan informal dengan menunjukkan bahwa legitimasi figur jago dibangun melalui kepercayaan sosial, pengalaman, dan pengakuan kolektif sehingga mendukung terciptanya keteraturan sosial dalam kehidupan warga binaan.